Domestic violence and employment: an examination into retail employer's awareness of and responses to the Impacts of domestic violence on the workplace - Kaunda, Nikiwe J (Institute of Development and Labour Law, 2024)
There is increased recognition that employees need to maintain a balanced work-home life in order to be successful and productive. One of the major threats to attaining this equilibrium is 'personal' issues such as HIV/AIDS, trauma and domestic violence. Such issues not only have economic impacts on a business' bottom line, but there are _·also social impacts that affect employment relations. The problem is further compounded by the difficulties that employers face in determining first the manner in which social problems become 'workplace' problems, and secondly, in deciding how they can meaningfully intervene. Because of the difficulties employers face in transcending the perceived boundaries between 'public' and 'private' concerns, some of these social problems are not effectively addressed, even though they may have negative impacts on a business. This research provides an expose of the manner in which domestic violence related issues are perceived and dealt with in the South African workplace. The research specifically focuses on establishing whether employers in the clothing, footwear and textile (CFf) retail sector are aware of the impacts of domestic violence on workplace relations. Findings suggest that the first step towards resolving such problems lies first in the ability of employers to identify the manner in which a social problem impacts on a business, and, secondly determining the best way in which employers can utilise existing resources and liaise with social service providers to address these concerns. Domestic violence is a prevalent social problem that requires the intervention of all segments of society. Employers need to start acting now, before the debilitating effects begin to disrupt workplace productivity on a larger scale.